(untitled) (Research, Society and Development, 2025)
Endodontics is a specialized dental field focused on diagnosing and treating diseases affecting the dental pulp. A fundamental aspect of successful endodontic therapy is root canal obturation, which aims to seal the canals and prevent reinfection. The choice of obturation materials is critical, requiring biocompatibility, durability, and effective sealing ability, especially in humid environments where moisture can compromise material performance and lead to treatment failure. Common materials include gutta-percha and various sealing materials, such as resin-based and bioceramic sealers, which offer improved adhesion, sealing, and mechanical resistance. Recent advancements have introduced innovative materials and obturation techniques, such as thermoplasticized gutta-percha systems (e.g., Thermafil) and synthetic alternatives like Resilon, which create a monoblock effect for enhanced sealing. Hydraulic cement sealers have gained popularity due to their antimicrobial properties and interaction with moisture during setting. Research highlights the importance of selecting appropriate materials and methods to optimize sealing quality, reduce microleakage, and enhance the mechanical integrity of obturations. Complex root canal anatomies, including oval-shaped canals and anomalies like dens invaginatus, pose challenges that require advanced imaging techniques such as cone beam computed tomography (CBCT) for accurate diagnosis and treatment planning. Future directions in endodontic obturation focus on bioactive and antimicrobial materials, nanotechnology, and 3D printing to improve material performance, longevity, and biological integration. These innovations aim to facilitate regenerative, minimally invasive treatments that promote tissue healing and long-term tooth preservation.